Analysis of aerobic and anaerobic abilities in elite junior cross-country skiers: a preliminary report - Flacco, L.; Pietrangelo, T.; Di Tano, G.; Bertollo, M.; Fanò, G. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
The cross-country ski is a winter endurance sport known for the requirement of specific aerobic skill. This sport is also characterised by repetitive and cyclic movements based on prolonged and maximal exertions. This discipline requires specific technical movements linked to the presence of the snow. Due to the absence of snow during the year, the athletes needs to train utilising different approaches and using a non-specific modalities. This paper is a part of abroad evaluating process, that concern: physiological, psychological, kinesiological and motor analysis of performance in junior elite skiers from Abruzzo. The sample was composed of 18 athletes. The general aims of this investigation is to define performance profile of junior elite skiers and monitoring their performance. The purpose of the present study was to investigate the aerobic and anaerobic power in order to 1) measure the efficiency of the training, 2) evaluate the reliability of performed tests and 3) evaluate the correlation between different methods of measurement. In particular this study is based on measurements carried out from 6 male subjects during the classic (general, preagonistic and agonistic) training periods. All subjects were competing at the collegiate or national levels; each skier reviewed and signed consent form prior to participating. The anthropometric characteristics of selected skiers were (average ± SD): 16.2±1.2 (age), 171.5±3.1 (cm, height), 68.0±7.3 (Kg, body mass), 18,5±1,7 (% body fat). The aerobic power (VO2max) was evaluated by K4b2 (Cosmed, Roma, Italy) and the averaged VO2max was 64.11±1.6 ml Kg-1 min-1. The anaerobic power (1,740±0,152 KW) was recorded using a jumping tests with Ergojump Bosco-Sistem (MAGICA, Roma, Italy) and Dynabiopsy apparatus (POLYMED, Sambuca-Firenze, Italy). This data was correlated with motor abilities test from eurofit battery (European test of physical fitness. Rome: Council of Europe, Committee for the Development of Sport, 1988). Statistical analysis of obtained data showed that all skiers showed an appreciable training level incremented during the training period and a good reproducibility for the tests used during the study. Some eurofit test was correlated with performance, aerobic and anaerobic power.